MANAJEMEN USAHA INDUSTRI KECIL MAKANAN TRADISIONAL (STUDI KASUS USAHA LEPAT BUGI ASLI IBU ELIS DANAU BINGKUANG KABUPATEN KAMPAR) - Anggraini, Desi; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research was conducted on the original bugis mother fast a business located in the village elis Kampar Regency Lake Jl. Pekanbaru cross-Bangkinang KM.34. The purpose of this study was to determine how the management of small businesses as a traditional food industry in Kampar Regency in many respects, namely financial management, human resource management, production management. This research is a descriptive qualitative approach. That where there is no population and sample. This study used interviews to obtain needed information. The data used is primary data and secondary data. The primary data of the results of interviews with business owners associated with the original bugis fast a business management elis mom. Secondary data is data that can be from field surveys. From the results of research conducted fast a business can be seen that the original bugis elis mom has been established since 2006 and now has opened branches namely: Branch Arifin Ahmad Pekanbaru Panam Side Branch Partner Betondi Garuda Sakti, Branch Jl. Hope Kingdom Edge Adira side after Sp. Red Light Bukit Barisan. Fast a genuine effort bugis elis mother has also been awarded recorded on the books of traditional food Kampar in 2008.Keywords: Business Management, Traditional Food, Financial Aspects, Aspects of Human Resources, and Production Aspects.